Manifestation of the Sacred in a short story O defunto (1895) by Eca de Queiroz (1845-1900): The intervention of Our Lady of Pilar - Rocha, Denise [UNESP] (Pontificia Univ Catolica Sao Paulo-puc-sp, 2021)
In the third phase of his literary production, Jose Maria Eca de Queiroz (1845-1900) devotes himself to the writing of religious content works - hagiographies and divine manifestations -, among others. Based on an exemplary narrative, mentioned in Sermao XXV de Maria, Rosa Mistica, by Padre Antonio Vieira, Eca writes the short story, O defunto (1895), about the power of the rosary prayer and the help provided by Our Lady of Pilar. The topic of praise of the Virgin and her miracles is preserved in the literary tradition of the Peninsula, and was perpetuated in Cantigas de Santa Maria, y Afonso X, The Wise (1221-1284)
Keywords: Portuguese Literature; Eca de Queiroz; O defunto; Sacred; Our Lady of Pilar